Analysis of Sustainability Report Disclosure and Company Size on Financial Performance in State-Owned Enterprises (BUMN) Listed on the Indonesia Stock Exchange (IDX) for The Years 2020-2024 - Dinaroh Dinaroh; Maiyaliza Maiyaliza (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the influence of Sustainability Report (SR) disclosure and Company Size on Financial Performance in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Using a quantitative approach with multiple linear regression analysis, this study examined 15 BUMN companies over five years (75 observations). The findings reveal that SR disclosure has a significant but negative effect on Net Profit Margin (NPM), with a coefficient of -73.421 (p = 0.008), suggesting that sustainability reporting initiatives impose short-term financial costs before generating long-term benefits. Conversely, Company Size does not have a significant effect on financial performance (p = 0.754). While the model demonstrates simultaneous significance (F-test, p = 0.027), the Adjusted R² value of 0.070 indicates that only 7% of variation in financial performance is explained by these two variables, highlighting the need for more comprehensive model specification. This research contributes to the sustainability accounting literature by presenting empirical evidence that challenges the assumption that sustainability disclosure automatically enhances short-term profitability, particularly in the context of state-owned enterprises facing dual mandates of profit generation and public service delivery. Future research should extend the model using panel data methods (Fixed Effects or Random Effects models), incorporate additional variables such as corporate governance indicators and financial structure measures, and examine sector-specific and long-term effects of sustainability disclosure.